Effects of two coatings on the quality of papaya (Carica papaya) variety tainung - Abraham Miranda; Armando Alvis; Guillermo Arrazola (Temas Agrarios, 2014)
The effect of the application of coatings based on cassava starch and one commercial in the conservation of papaya (Carica papaya) Tainung variety was compared. The coating cassava starch used was prepared with a concentration of 4% p/v; the concentration of the commercial wax was prepared by diluting one part of wax to one part of water at room temperature according to the manufacturer's recommendations. Papayas are stored lying down (stalk parallel to the surface), at room temperature (22°C ± 2°C) and 85% relative humidity for a period of 9 days. In the study of the effect of the wax in papayas, there was only statistically significant (P<0.05) on the variables: pH and firmness, also the interaction between waxed and time factors was highly significant in variables: pH, °Brix and firmness. Besides, in the effect of time on all observed variables (pH, °Brix, acidity (%), mass loss and firmness) there was a statistically significant difference (P<0.05). Finally, it was concluded that in both coatings and control did not differ significantly in acidity, soluble solids and mass loss, however these were different to the control on the behavior of the firmness and texture.